The aspectual semantics of the independent subjunctive in Latin - Чернюх, Богдан Васильович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The temporalization of the Latin verb system contributed to the fact that in the historical time the subjunctive primarily functions in the plane of modality and temporality, while the aspectual component is mentioned only in passing. Thereby the question of the aspectual semantics of the forms of the subjunctive and its relation to the old aspect-modal and later temporal-modal types of values arises. The analysis of the aspectual semantics of the independent subjunctive in Latin allows to confirm that unlike the indicative mood with its opposition of imperfecum and perfectum tenses, there is no such regular one in subjunctive. The above mentioned opposition in subjunctive is occasional strongly depending on actional semantics of predicates and character of context. The atelic predicates tend to express imperfectivity, and the telic ones have mainly perfective meaning. Coniunctivus perfecti and plusquamperfecti of atelic predicates allows double interpretation i.e. limitative or ingressive one. The aspectual distinction of infectum and perfectum forms of subjunctive sometimes seems to be blurred. It is typical for the predicates with similar actional features as well as for the verb “esse”. In such a case the telic predicates stress the seme of completivity, while the atelic ones the seme of limitativity. These factors affect deeply the members of infectum subsystem, which are aspectual-neutral and can have imperfective as well as perfective meaning. The members of perfectum subsystem on the contrary are perfective marked. They express ceased situations which depending on context can be interpreted as punctive, inceptive or limitative ones.